Altered expression of hyaluronan, HAS1‐2, and HYAL1‐2 in oral lichen planus. (25th November 2014) - Siponen, Maria; Kullaa, Arja; Nieminen, Pentti; Salo, Tuula; Pasonen‐Seppänen, Sanna
<x xml:space="preserve">Abstract</x> Background Oral lichen planus (OLP) is an immune‐mediated mucosal disease of unclear etiology and of unresolved pathogenesis. Hyaluronan (HA) is an extracellular matrix glycosaminoglycan involved in inflammation and tumor progression. However, its presence in OLP has not been reported. We therefore aimed to study the immunohistochemical expression of HA, its receptor CD44, hyaluronan synthases (HAS1‐3), and hyaluronidases (HYAL1‐2) in OLP. Methods The presence of HA, CD44, HAS1‐3, and HYAL1‐2 was studied by immunohistochemical methods in 55 OLP and 23 control oral mucosal specimens (CTR). The localization, intensity, and differences of the epithelial expression between OLP and CTRs were analyzed. Results HA and CD44 were found on cell membranes in the epithelial basal and intermediate layers in CTR and OLP specimens. The HA staining intensity was stronger in the basal layer of the epithelium in OLP than in CTRs (P < 0.001). HAS1 (P = 0.001) and HAS2 (P < 0.001) showed stronger staining in the basal and weaker staining in the superficial (P < 0.001) epithelial layers in OLP than in CTRs. The immunostaining of HAS3 was low in both OLP and CTRs. Positive HYAL1 and HYAL2 staining were mainly found in the basal and intermediate epithelial layers, and their intensities were significantly increased in OLP, except HYAL 2 in the intermediate epithelial layer. Conclusions HA, HAS1‐2, and HYAL1‐2 have altered expression in OLP compared to CTRs and may therefore have a role in OLP pathogenesis.